MRI does not predict pathologic complete response after neoadjuvant chemotherapy for breast cancer. Issue 6 (9th August 2019) - Sener, Stephen F.; Sargent, Rachel E.; Lee, Connie; Manchandia, Tejas; Le‐Tran, Vivian; Olimpiadi, Yuliya; Zaremba, Nicole; Alabd, Andrew; Nelson, Maria; Lang, Julie E.
Abstract: Background: This study assessed whether magnetic resonance imaging (MRI) could accurately predict pathologic complete response (pCR) after neoadjuvant chemotherapy (NAC) for patients receiving standardized treatment, pre‐ and post‐NAC MRI on the same instrumentation using a consistent imaging protocol, interpreted by a single breast fellowship‐trained radiologist. Methods: A single‐institution retrospective analysis was performed including clinical, radiographic, and pathologic parameters for all patients with breast cancer treated with NAC from 2015 to 2018. Radiographic complete response (rCR) was defined as absence of suspicious MRI findings in the ipsilateral breast or lymph nodes. pCR was defined as the absence of invasive cancer or ductal carcinoma in‐situ in breast or lymph nodes after operation (ypT0N0M0). Results: Data for 102 consecutive patients demonstrated that 44 (43.1%) had rCR and 41 (40.1%) had pCR. pCR occurred in 12 (25.0%) of 48 estrogen receptor positive (ER+) patients, 29 (53.7%) of 54 ER− patients, and 25 (52.1%) of 48 human epidermal growth factor receptor 2 positive patients. The positive predictive value for MRI after NAC was 84.5% and the negative predictive value was 72.7%. The accuracy rate for MRI was 78.6%. Of the 44 patients with rCR, 12 (27.3%) had residual cancer on the pathologic specimen after surgical excision. Conclusion: rCR is not accurate enough to serve as a surrogate marker for pCR on MRI after NAC.